The Differences between Self Concept and Emotional Intelligence (in Terms of Gender) - Agustiyana, Ali Sunarso, Sintya Ayu (Universitas Negeri Semarang, 2018)
The background of this research was the low self-concept and emotional intelligence of students. The research was aimed to describe the self concept and emotional intelligence of students and determine the different of self concept and emotional intelligence of students in terms of gender.The desaign was comparative research. There were 64 students as sample, divided into 40 male students and 24 female students. Data conducted using a quisionere by likert scale. The results showed that self-concept students in high category and students' emotional intelligence was high. The results of self-concept t-test analysis obtained t value (1.051849) t tableÂ (1.9998). In t test of emotional intelligence obtained t value (-1.82245) t table (1.9998). The conclusion of this research is there were no differences in self concept and there were no differences in emotional intelligence of student in SDNÂ Gugus Ki Hajar Dewantara between maleÂ and female students.